Website Desa Pendampingan Perancangan Website Sebagai Media Informasi dan Promosi Desa Wisata Kalipucang Kecamatan Tutur Kabupaten Pasuruan - Subchan Asy’ari (LPPM Universitas Yudharta Pasuruan, 2021)
Kalipucang Village is one of the villages in the Tutur sub-district, Pasuruan Regency. The village is one of the villages that has extraordinary natural and educational potential. There are four destinations which include two nature tours, namely the waterfall source Nyonya, Tumang hill, and two educational tours, namely milk village and coffee village tours. Rows of sturdy and beautiful mountains make tourists interested in traveling there. There are six hamlets in Kalipucang village, namely South Kuntul Hamlet, North Kuntul Hamlet, Dodogan Hamlet, Mucangan Hamlet, Cikur Hamlet, and Jelag Hamlet. The Kalipucang Village area is located in a highland area with an altitude of 840 meters above sea level and a place of ​​671.178 hectares and has a population of 4,272 people. So far, this extraordinary potential has not been published or promoted through websites and social media to boost more visitors, especially since most visitors see references first before coming directly. Natural resources and educational tours owned by human resources who are technologically savvy will make the potential of nature unknown to the broader community. The apparatus in Kalipucang Village has a maximum education of High School, and only a few people can take the lecture bench. This is where the anxiety experienced by the Kalipucang village government is that they have not been able to publicize their area. It is only limited to educational tours that have been published. However, for the natural potential, it has not been published because of the lack of knowledge about the benefits of the internet (online media).